Constitutionalism and the Debate Surrounding the Suspension of the Advocates’ Association - Lutfiadi, Lutfiadi; Wardani, Win Yuli; Heryanti, Febrina; Camelia, Noer Dini; Purwandi, Agustri (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The suspension of advocates’ Oath of Office (BAS) by the High Court raises significant concerns within the framework of Indonesian procedural law and state administration. The core issue stems from the absence of an explicit legal basis authorizing such action, which may contravene the principles of legality, constitutionalism, and the protection of advocates’ fundamental rights. This study aims to examine the legal legitimacy of the BAS suspension, evaluate its compliance with constitutional principles, and explore its philosophical implications for the role of advocates as law enforcers on a par with judges, prosecutors, and police officers. Employing a normative juridical approach with a focus on doctrinal analysis of the Advocates Law, the 1945 Constitution, relevant court decisions, and legal literature, the study finds that the BAS suspension constitutes an ultra vires act. Consequently, this measure undermines the rule of law, diminishes the independence of the legal profession, and has the potential to disrupt public access to justice, highlighting the need for more robust regulatory reforms.